SINGLE DOSE CAUDAL TRAMADOL VERSUS BUPIVACAINE FOR POSTOPERATIVE ANALGESIA IN PERINEAL SURGERY: Postoperative Analgesia in Perineal Surgery - Bhutta, Irtiza Ahmed; Tariq, Muhammad (Pakistan Armed Forces Medical Journal, 2009)
Objective: To compare the postoperative analgesic effects of caudally administered Tramadol and Bupivacaine in adults undergoing perineal surgery. Study Design: Randomized control trail. Place and Duration of Study: Department of Anaesthesia Combined Military Hospital Quetta from July 2001 to June 2003. Patients and Methods: A total of 100 adult patients undergoing perineal surgery, aged 20-50 years, American Society of Anaesthesiology (ASA) 1 and 2 were included. The patients were divided into two equal groups. Group B was given 20 ml 0.25% Bupivacaine while the group T was given 100mg Tramadol through caudal route after induction of general anaesthesia. No other analgesic was given intraoperatively. The postoperative pain was evaluated by using visual analogue scale (VAS) at immediate postoperative period and then every hour for first 12 hours. Pulse rate, blood pressure, O2 saturation (SpO2), respiratory rate, expired CO2 (ETCO2) and any side effects were monitored. The cut-off point for study was VAS 6, when additional analgesic was administered. Results: Caudally administered Bupivacaine and Tramadol provided good postoperative analgesia but mean duration of analgesia was longer in group B (10.5±2.02 hrs) compared to group T (7.14±1.77 hrs). There were no clinically significant haemodynamic and respiratory changes observed in either group; however nausea and vomiting were more in group T. The demand for supplemental analgesia was more in the patients belonging to T group than B group. Conclusion: Bupivacaine and Tramadol are safe when used caudally in adults but Bupivacaine provided longer and better quality of postoperative analgesia than Tramadol after perineal surgery.